Endoscopic sleeve gastroplasty with 1-year follow-up: factors predictive of success - Lopez-Nava, G.; Galvao, M.; Bautista-Castaño, I.; Fernandez-Corbelle, J. P.; Trell, M. (Endoscopy International Open, 2016)
Background and study aims: Bariatric endoscopy has emerged as an aid in the nonsurgical treatment of obesity. The objective of this study is to critically provide the results and follow-up of endoscopic sleeve gastroplasty 1 year after the procedure. Patients and methods: Prospective single-center follow-up study of 25 patients (5 men, 20 women) who underwent flexible endoscopic suturing for endoluminal gastric volume reduction. A multidisciplinary team provided post-procedure care. Patient outcomes were recorded at 1 year after the procedure. Linear regression analysis was done to evaluate the variables associated with best results at 1 year of follow-up.Results: Mean body mass index (BMI) was 38.5 ± 4.6 kg/m2 (range 30 – 47) and mean age 44.5 ± 8.2 years (range 29 – 60). At 1 year, 22 patients continued with the follow-up (2 dropped out at 6 months and 1 at 3 months). There were no major intra-procedural, early, or delayed adverse events. Mean BMI loss was 7.3 ± 4.2 kg/m2, and mean percentage of total body weight loss was 18.7 ± 10.7 at 1 year. In the linear regression analysis, adjusted by initial BMI, variables associated with %TBWL involved the frequency of nutritional (β = 0.563, P = 0.014) and psychological contacts (β = 0.727, P = 0.025). The number of nutritional and psychological contacts were predictive of good weight loss results. Conclusions: Endoscopic sleeve gastroplasty is a feasible, reproducible, and effective procedure to treat obesity. Nutritional and psychological interaction are predictive of success.